New records of rarely reported species in the Mediterranean Sea (March 2025) - JOSÉ CARLOS BÁEZ; OKAN AKYOL; ERNESTO AZZURRO; PIETRO BATTAGLIA; ANGEL BELMONTE-GALLEGOS; GEORGIOS CHRISTIDIS; FABIO CROCETTA; CEM DALYAN; YUNUS GÖNÜL; FABIO GRATI; SILVESTRO GRECO; CHRYSOULA GUBILI; et al. (Mediterranean Marine Science, 2025)
This collective study presents information on fifteen (15) species recorded across five countries (Greece, Italy, Slovenia, Spain, and Türkiye) and four (4) ecoregions, ranging from the Alboran Sea to the Aegean Sea. The recorded species belong to three phyla: Mollusca (3 species), Arthropoda (3 species), and Chordata (9 species). Among mollusks, Martadoris mediterranea is reported for the first time in the Aegean Sea at two different locations, while Opisthoteuthis calypso and Octopoteuthis sicula are newly recorded in the western Mediterranean. Regarding arthropods, Ocypode cursor is reported from the Tyrrhenian coast of Sicily, Pachygrapsus transversus is recorded for the first time in the Tyrrhenian Sea, and Cancer pagurus in the Sea of Marmara. Among chordates, Lobotes surinamensis and Zu cristatus are newly recorded in the Alboran Sea, while Callionymus fasciatus and Symphodus doderleini are reported from Slovenian coastal waters. Tripterygion delaisi and Gymnothorax unicolor are documented for the first time in the waters of the Sea of Marmara and Crete, respectively. Additionally, new records of rarely reported fish species include Arctozenus risso, Chromogobius zebratus, and Epinephelus aeneus in Turkish, Spanish, and Italian waters, respectively.